2022
DOI: 10.1111/1468-4446.12940
|View full text |Cite
|
Sign up to set email alerts
|

One foot on shore: An analysis of global millionaires' demand for U.S. investor visas

Abstract: Each year, around 10,000 foreigners obtain a U.S. residence visa after investing half a million dollars or more.Who are the millionaires that acquire these visas and what motivates them to leave their home countries? To answer this question, I analyzed an original data set that combines U.S. visa statistics with data on global millionaire populations. The analysis produced three key findings. First, demand for investor visas was led by millionaires from countries that ranked lower in the global hierarchy of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In Portugal and Greece, for example, the Golden Visa program has surpassed traditional industries such as tourism and manufacturing as the principal source of foreign direct investment (Schacherer, 2022). Despite the fact that the majority of this investment has come from Chinese investors, the Golden Visa program in the United States (US) aided the country in stabilizing its economy throughout the pandemic (Harpaz, 2022). Golden Visa schemes, without a doubt, have been shown to have a favorable overall influence on national economies.…”
Section: Introductionmentioning
confidence: 99%
“…In Portugal and Greece, for example, the Golden Visa program has surpassed traditional industries such as tourism and manufacturing as the principal source of foreign direct investment (Schacherer, 2022). Despite the fact that the majority of this investment has come from Chinese investors, the Golden Visa program in the United States (US) aided the country in stabilizing its economy throughout the pandemic (Harpaz, 2022). Golden Visa schemes, without a doubt, have been shown to have a favorable overall influence on national economies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, David Ley's (2011) analysis of the former Canadian programme found that investment migrants' motivations were not necessarily economic, but often involved the search for a quieter pace of life and high-quality education for their children. Analysing the US investor visa programme, Harpaz (2022) finds that visa applications increased when measures of the 'quality of democracy' in the country of origin deteriorated, suggesting that investor visas provided a 'plan B' for wealthy elites in authoritarian regimes. Other studies have found that some investor programme participants (in both CBI and RBI programmes) are not necessarily interested in settling in a new country but want to gain what Surak (2016, p34) calls "extra-territorial" benefits, such as visa-free travel to other countries (Montezuma & McGarrigle, 2019;Van der Baaren & Li, 2018).…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…Another commonly cited motivation is to secure a second residence status or citizenship as an insurance policy, in the face of political or economic uncertainty at home, even if applicants do not immediately plan to move (Tseng, 2000;Montezuma and McGarrigle, 2019;Surak, 2020;Harpaz, 2022). Successful business people living in countries with autocratic regimes, for example, may have no need to move in the present but want a plan B in case the political climate turns against them; external geopolitical threats could also play a role (e.g.…”
Section: Extra-territorial Benefits and Investor 'Non-migrants'mentioning
confidence: 99%